Symptoms and stool patterns in patients with ulcerative colitis. - Rao, S S (1988)
The prevalence of symptoms and stool patterns was assessed prospectively in 96 patients with ulcerative colitis subdivided according to the extent and activity of the disease. Increased frequency of defecation (83%), urgency (85%), a feeling of incomplete evacuation (78%) and tenesmus (63%) were the most frequent symptoms experienced by patients with active colitis. All were significantly more common (p less than 0.001) in patients with active than quiescent colitis and their prevalence was similar in those with total and distal colitis, indicating that these symptoms are related to an inflamed and irritable distal colon. Twenty seven per cent of patients with active colitis voided hard stools indicative of constipation, however, and this was more common in active, than quiescent colitis (p less than 0.05). This feature is probably secondary to faecal stasis in the proximal colon, and an apt description of the bowel disturbance in ulcerative colitis, irrespective of the extent of disease is that the colon suffers from proximal constipation and distal irritability.